Uma ilha na imprensa brasileira: o olhar do jornal Diário de Notícias (RS) sobre a revolução cubana - Sabadini, Geanine (2014)
This monograph is the result of research conducted in the newspaper Diário de Notícias(RS), representative of the mainstream media about the news and articles about the Cuban Revolution aired between 1958 and 1960. In three years time block analyze the reception of the Cuban revolutionary process and the image that this periodic spread over Cuba in Brazil. We also consider the production of books and articles of intellectuals who addressed the issue of the Cuban Revolution, the press, the Cuban relations with Brazil and Latin America, the influence of the Cuban process in the Brazilian and international political struggle, and revolutionary leaders such as Fidel Castro and Ernesto "Che" Guevara, among other topics discussed over the years in which the journal highlighted this process. The objective of this paper is to analyze the contents of the newspaper Diário de Notíciasreferring to the Cuban Revolution, in order to know the representations and interpretations of this journal provided the Brazilians, as well as the image that the newspaper traced the Caribbean island and the controversies that have arisen. Thus, this study also seeks to identify the processes of construction of the images and statements pertaining to the Cuban Revolution, with the subsequent establishment of positions on the issue; analyze the motivations of these positions and descriptions to characterize the ideologies present in the discourse of the newspaper, understand the debates generated in Brazil about the episodes lived in Cuba and interpret the possible repercussions of those events in Brazilian society and culture soil. Therefore, we analyze some methodological aspects combined the results of research in the press. More than a comparative history, we seek a connective story that goes beyond the causal elements and effect and to work with multiple worlds: the soviet socialist, capitalist american and latinamerican. We conducted a brief history about the newspaper Diário de Notícias and at the end of the paper, we analyze representations of the journal about different aspects of the revolutionary process, and how they contributed to the construction of the image of the revolution in brazilian public opinion.